A 'BUSINESS' FLOW CHART AND ITS USE AS A TEACHING AID. - Schönfeld, Hanns-Martin; Holzer, H. Peter (The Accounting Review, 1962)
Abstract The many approaches used in introducing a beginning student to the field of business seem to indicate that finding an appropriate first course in business is one of the more difficult aspects of curriculum planning. Such a course, in addition to acquainting the student with the basic concepts of business, should also teach the various interrelationships between the various functions within a business and the basic relations of a business with other segments of the business world. Since most students specialize in one function during the later years of their academic training it certainly seems important to give them an integrated view of a business entity as early as possible. The beginning course in accounting is an ideal vehicle for introducing students to basic concepts and interrelationships of the business world. In this paper we propose a "flow chart" which might be used effectively as a teaching tool in several beginning courses of business including the first course in accounting. This chart, used as a visual aid device, should help students attain the aforementioned objectives of introductory courses. In later accounting courses the chart might also prove useful in the presentation of fund statements and cash flow statements.